Fabrication and photoelectrochemical properties of silicon/nickel oxide core/shell nanowire arrays. Issue 107 (16th October 2015) - Zhang, Fu-Qiang; Hu, Ya; Meng, Xiang-Min; Peng, Kui-Qing
Abstract : A photoelectrochemical (PEC) cell made of a silicon nanowire array coated with a thin nickel oxide (NiO x ) shell layer for solar water oxidation is presented. Abstract : A photoelectrochemical (PEC) cell made of a silicon nanowire array coated with a thin nickel oxide (NiO x ) shell layer for solar water oxidation is presented. The silicon/NiO x core/shell nanowire photoanodes are fabricated by a simple and scalable one-step galvanic displacement reaction and thermal annealing. The conformal NiO x shell layer functions as an oxygen evolution catalyst to reduce the onset potential as well as a protection layer against corrosion. It was found that about 30 nanometer thick NiO x film coated p-type silicon nanowire arrays exhibited efficient water oxidation activity with stability for more than 48 h in aqueous Na2 SO4 solution (pH ∼ 7). The scalability of this approach is promising for the fabrication of Si-based photoelectrodes.